Implementasi Manajemen Berbasis Sekolah Sebagai Strategi Pemberdayaan dan Penguatan Pendidikan Karakter SDN 1 Citalang Kecamatan Purwakarta - Aris Purwadin; Atik Kurniawati; Iin Sinta; Alwin Mujaiyanah; Nita Nurbaeti; Nisa Lutfi; Faiz Karim Fatkhullah (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study aims to describe and analyze the implementation of School Based Management (SBM) at SDN 1 Citalang as a strategy for empowerment and character education strengthening. Using a qualitative approach with a case study design, data were collected through in depth interviews with the principal and a teacher, participant observation, and documentation studies. Data analysis followed Miles and Huberman's interactive model involving data reduction, display, and conclusion drawing. Findings reveal that SBM implementation has been effectively executed through the integration of culturally grounded character programs, particularly the "7 Poe Atikan Istimewa" policy which embeds daily activities reinforcing nationalism, literacy, Sundanese local wisdom, social care, and spirituality. The principal applies a democratic situational leadership style characterized by participatory decision making and bidirectional communication via face to face meetings and digital platforms. Key supporting factors include active participation of school members, strong local government policy legitimacy, and collaborative leadership. Major challenges involve physical infrastructure limitations (12 classrooms for 687 students necessitating shift systems), low digital capacity among teachers (only 35% proficient in LMS), and parental traffic management. The study concludes that SBM serves as an effective framework for school management when implemented contextually with adaptive leadership and community participation, though sustainability requires continuous external support for infrastructure development and human resource capacity building.